The Risk‐Adjusted Cost of Financial Distress - ALMEIDA, HEITOR; PHILIPPON, THOMAS (Journal of Finance, 2007)
ABSTRACT Financial distress is more likely to happen in bad times. The present value of distress costs therefore depends on risk premia. We estimate this value using risk‐adjusted default probabilities derived from corporate bond spreads. For a BBB‐rated firm, our benchmark calculations show that the NPV of distress is 4.5% of predistress value. In contrast, a valuation that ignores risk premia generates an NPV of 1.4%. We show that marginal distress costs can be as large as the marginal tax benefits of debt derived by Graham (2000) . Thus, distress risk premia can help explain why firms appear to use debt conservatively.